2015
DOI: 10.1111/jphp.12412
|View full text |Cite
|
Sign up to set email alerts
|

ShenKang injection suppresses kidney fibrosis and oxidative stress via transforming growth factor-β/Smad3 signalling pathway in vivo and in vitro

Abstract: SKI inhibits renal fibrosis and oxidative stress through downregulation of TGF-β/Smad3 signalling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 33 publications
2
28
0
Order By: Relevance
“…One of the affected cytokines is TGF‐β, which has been shown to play a pivotal role in enhancing extracellular matrix synthesis. The enhanced production of collagen, in particular, is associated with the progression of fibrosis . The results of the present study showed that sorbitol levels were higher in the LF tissue from DM (+) patients than in that from DM (−) patients, and that the LF in the DM (+) patients was significantly thicker than that in the DM (−) patients.…”
Section: Discussionsupporting
confidence: 41%
See 3 more Smart Citations
“…One of the affected cytokines is TGF‐β, which has been shown to play a pivotal role in enhancing extracellular matrix synthesis. The enhanced production of collagen, in particular, is associated with the progression of fibrosis . The results of the present study showed that sorbitol levels were higher in the LF tissue from DM (+) patients than in that from DM (−) patients, and that the LF in the DM (+) patients was significantly thicker than that in the DM (−) patients.…”
Section: Discussionsupporting
confidence: 41%
“…The enhanced production of collagen, in particular, is associated with the progression of fibrosis. 20,21 The results of the present study showed that sorbitol levels were higher in the LF tissue from DM (þ) patients than in that from DM (À) patients, and that the LF in the DM (þ) patients was significantly thicker than that in the DM (À) patients. These findings suggest that increased levels of hyperglycemia-induced sorbitol may contribute to LF hypertrophy in DM (þ) LSCS patients.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…In addition, Klotho was reported to inhibit transforming growth factor‐β1 (TGF‐β1) signalling by directly binding to TGFβ‐RII, this is a vital mechanism for Klotho‐mediated prevention of renal fibrosis 7. TGF‐β1 has been identified as the key profibrogenic cytokine via activating downstream mediators, especially Smad proteins, and finally regulating ECM production 8. Thus, blocking the Klotho/TGF‐β/Smad signalling pathway may be promising for preventing renal fibrosis and preserving renal function.…”
Section: Introductionmentioning
confidence: 99%